ANALISIS HUKUM PENCEMARAN YANG TELAH TERBUKTI MELALUI UJI BAKU MUTU LINGKUNGAN AGAR DAPAT MENJADI DASAR BAGI PENEGAKAN HUKUM PIDANA LINGKUNGAN - Hermansyah, Danu; Erdianto, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Environmental law is a field or branch of law that has special characteristics which drupsteen calls the functional law field (functioneel rechtsgebeid), in which there are elements of administrative law, criminal law and civil law. Therefore, the enforcement of environmental law can be interpreted as the use or application of instruments and sanctions in the field of administrative law, criminal law, and civil law with the aim of forcing the subject of law subject to compliance with environmental legislation.This research is a normative legal research, because it is based on library research that takes excerpts from reading books, literature, or supporting books that have relation to the problem to be studied, assisted with primary, secondary and tertiary data sources. This study uses qualitative data analysis and produces descriptive data.From the results of the study, it was concluded that, First, Pollution that has been proven through environmental quality standard tests can be the basis for environmental criminal law enforcement that must meet at least 3 elements, namely: the existence of an unlawful nature (wederrechtelijk), an error (schuld), and only then then the application of a criminal (strafe). These elements can already be used as a basis in the enforcement of environmental criminal law against corporations that have dumped waste into rivers and exceed the threshold for environmental quality testing. Second, the factors that affect pollution that have been proven by environmental quality standard tests can be the basis for the investigation of environmental crimes, which is to prove a criminal act of environmental pollution such as river pollution is not necessarily easy to prove, it must require proof that is truly accurate and valid. namely through expert information and one of the important aspects that can affect the effectiveness and efficiency of environmental management in a country is whether or not an accredited laboratory is available, in this case an environmental laboratory capable of producing data that is valid and reliable, irrefutable, and can be accounted for in an effective manner scientifically as well as legally.Keywords: Pollution, Quality Standards Test, Criminal Law Enforcement